An Analytical Study of Science Students’ Attitudes Toward Environmental Conservation Issues and Actions - Kesumajayadi, Lalu; Farisi, Salman Al; Sumarlin, Muhamad; Wangiyana, I Gde Adi Suryawan (International Journal of Ethnoscience and Technology in Education, 2025)
This study aims to analyze science students’ attitudes toward environmental conservation issues and actions, with a focus on understanding personal commitment, emotional engagement, conservative values, and appreciation for environmental education. Employing a mixed-methods approach, quantitative data were obtained from 43 students through a five-point Likert-scale attitude questionnaire, while qualitative data were collected through in-depth interviews with six selected respondents. Quantitative analysis revealed an average attitude score of 24.56, categorized as "Low", with the majority of respondents (55.81%) showing a weak level of concern toward environmental conservation issues. No respondents fell into the "Very Good" category, and only 6.98% were classified as "Good". The qualitative analysis indicated that, although students expressed normative awareness of the importance of conservation, their involvement remained situational, influenced by social context, and constrained by academic pressure and limited community support. The findings emphasize the need for reform in environmental education at the university level, particularly in integrating affective dimensions, personal values, and psychosocial empowerment. The implications highlight the importance of a transformative and participatory curriculum to foster strong and sustainable pro-environmental attitudes among science students.